Longitudinal or transverse? How the unbounded quantity expressed by the Finnish partitive case relates to time - Huumo Tuomas (De Gruyter, 2022)
One important function of the Finnish partitive case is the expression of unbounded quantity. An unbounded quantity can consist of a homogeneous substance, expressed by a mass noun in the partitive singular, or of a multiplicity, expressed by the partitive plural. The opposite meaning with a bounded quantity is typically
expressed by the nominative or the accusative. The main purpose of this paper is to give an account of how such quantities, bounded or unbounded, relate to time. I argue that there are two main options, referred to as longitudinal and transverse quantity. A longitudinal quantity is conceptualized as parallel to the
time axis: it is distributed in time in such a way that its sub-quantities participate in the event consecutively, one after another, as in ‘Water was leaking from the pipe’ (mass) or ‘I was eating apples’ (multiplicity). In such expressions, the event is telic at the level of any conceivable sub-quantity. In other words, each sub-quantity (e.g., one apple) participates in one telic component event, in which it is fully affected. These consecutive component events then constitute a higher-order event, which can be telic or atelic depending on whether the longitudinal quantity is bounded (as in ‘I ate the apples’) or unbounded (as in ‘I ate apples’).
A transverse quantity, in contrast, is conceptualized as perpendicular to the time axis: all its sub-quantities participate in the event simultaneously. The event can be punctual (as in ‘I found mushrooms under the tree’) or durative (‘I was carrying mushrooms in my basket’). In this paper, I demonstrate how longitudinal
and transverse quantities are expressed by Finnish S and O arguments in the partitive vs. nominative/accusative, and how they contribute to the aspectual meaning of the clause.
Partitive Determiners, Partitive Pronouns and Partitive Case